Tough row to hoe : Woman in Nicaragua`s agricultural cooperatives - Institute for Food and Development Policy (San Francisco, US : Food First)
Women's work in agriculture--The agrarian reform and the cooperative movement--Factors that influence the integration of women into cooperatives--Women's participation in the agricultural work of the cooperatives--The participation of women in the management of cooperatives--The advantages and problems encountered by women cooperative members.
Keywords: COOPERATIVAS; AGRICULTURA; NICARAGUA; POLITICA AGRICOLA; PARTICIPACIÓN DE LA MUJER